Why RBE must be a variable and not a constant in proton therapy - Jones, B (British Institute of Radiology, 2016)
Purpose: This paper considers why the proton therapy relative biological effect (RBE) should be variable rather than constant. Methods: The reasons for a variable proton RBE are enumerated, with qualitative and quantitative arguments. The heterogenous data sets collated by Pagenetti et al and the more homogenous data of Britten et al are further analysed using linear regression fitting and RBE-inclusive adaptations of the linear quadratic (LQ) radiation model. Results: The in vitro data show RBE increasing as dose per fraction is lowered. In the Paganetti et al (2002) data sets, the differences between observed and expected effects are smaller when the linear quadratic model is used, but with such data heterogeneity firm statistical conclusions cannot be obtained. The more homogeneous data set shows an unequivocal variation in RBE with dose per faction. The in vivo data are inappropriate for assessments of late normal tissue effects in radiotherapy. Also, if there is the same degree of uncertainty in an RBE of 1.1 or in an RBE of 2-3 for C ions, the fractional and biological effective doses (BED) can vary considerably and be greater in the proton case. So, errors in RBE assignment are important for protons, just as with C ions. Conclusions: Further experimental programmes are proposed, including late normal tissue endpoints. Better RBE allocations might further improve proton therapy outcomes. Advances in Knowledge: This study provides a rigorous critique of the 1.1 RBE used for protons, from theoretical and practical standpoints. The data analysis shows that the linear quadratic model is more appropriate than simple linear regression. Comprehensive research programmes are suggested.